2020
DOI: 10.1186/s13033-020-00395-2
|View full text |Cite
|
Sign up to set email alerts
|

Youth unemployment and mental health: prevalence and associated factors of depression among unemployed young adults in Gedeo zone, Southern Ethiopia

Abstract: Background: The high rate of unemployment among young adults in Ethiopia, which was 25.3% in 2018, is a major social, and public health concern. The risk of mental health problems like depression is higher among the unemployed than among the employed. However, there was no study conducted on the prevalence and associated factors of depression among unemployed young adults in Ethiopia. Hence, this study was aimed to assess the prevalence and associated factors of depression among unemployed young adults in Gede… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Lack of social support can have a profound impact on the job search efforts of young adults. Numerous studies have shown that unemployment adversely affects the psychological and physical wellbeing of people (McKee-Ryan et al, 2005 ; Mousteri et al, 2018 ; Paul & Moser, 2009 ) and is particularly devastating for unemployed young adults (Mokona et al, 2020 ; Thern et al, 2017 ). Most of the job search literature has focused on job search behavior of the individual (see Hoye et al, 2015 ; Vansteenkiste et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of social support can have a profound impact on the job search efforts of young adults. Numerous studies have shown that unemployment adversely affects the psychological and physical wellbeing of people (McKee-Ryan et al, 2005 ; Mousteri et al, 2018 ; Paul & Moser, 2009 ) and is particularly devastating for unemployed young adults (Mokona et al, 2020 ; Thern et al, 2017 ). Most of the job search literature has focused on job search behavior of the individual (see Hoye et al, 2015 ; Vansteenkiste et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anticipation of economic shocks may cause mental illness such as mania. People living in poverty face substantial uncertainty and income volatility and complex financial portfolios, often without access to formal insurance; this might increase the risk of developing bipolar symptoms ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…23-28 The PHQ-9 was also validated 29-33 and used in several studies. 25-28 34-39 The scales were slightly adapted for administration in a phone survey. First, we asked participants whether they were alone in the room and if not, whether they could find a quiet space and/or make sure their phone speaker was off.…”
Section: Methodsmentioning
confidence: 99%